(untitled) (Journal of the College of Education for Women, 2019)
When the Italian fascist party leaded & access to the top of regime, it took BenitoMussolini as a post of Italian prime minister on 1922, that lead to rise the voices which needto find colonies of Italy, like other colonial countries, especially that of its colonies in Libya,Eritrea and Somalia were not achieved its ambitions, was to be the occupation of Ethiopia torevive her dreams to exert control over the Red sea and the Mediterranean and theestablishment of a vast empire satisfy colonial ambitions.the Italian invasion of Ethiopia gained particularly important, what led to thedisruption of the balance of political forces is not at the level of local powers in the region,but at the level of the extended diagonals on the west coast of the red sea and horn of Africa.Egypt had a clear position from the occupation of what connects Ethiopia common interests,particularly the source of the river Nile.The research which divided in to the introduction, two sections, and conclusion, takingthe first section of the Egyptian official position of the Italian occupation of Ethiopia, andeconomic sanctions against Italy, while the second topic addressed the Egyptian popularposition of the Italian occupation of Ethiopia.The research depend on a variety of sources documents come in the forefront,including documents unpublished in the library and archives in Baghdad, the British and thedocumentation is not published, as well as published documents, which was the documentarybooks, as research on Arab and foreign sources, newspapers and magazines adopted.The Egyptian-Italian relations took a gradual decline in the wake of the Italianoccupation of Ethiopia in 1935, and was the Egyptian official position is identical with theBritish position, at the beginning of it, but it evolved over the public pressure to standopposed to the occupation, especially after realizing Egyptian politicians that control of Italyto Ethiopia means of control Lake Tana, source of the Nile and then it will be the lifeblood ofEgypt is vital, however, Italy, not to mention the control of Italy to Libya, and that means theoccurrence of Egypt between pliers Italy, so what that floated the idea of economic sanctionsagainst Italy until the Egyptian government announced its acceptance to apply thosesanctions, despite the lack of participation membership in the nations league, but they saw theU.N. resolution only door that it can stand against the Italian expansion. He was to participatein the Egyptian penal significant role in disturbing the relations with the Italians, who claimedthat they understands the Egypt’s position on the grounds that he came according to what youwant Britain.Was a popular position Egyptian prominent role in the Italian war Ethiopian, as opposedstrongly the Italian occupation of the Egyptians felt the seriousness of the occupation on theirlives and their future, and they keep their best to share with Ethiopians to repel the Italianaggression and demonstrated dramatically by sending material and humanitarian aid toEthiopia was the Egyptian medical missions a big role to help the war-wounded from theEthiopians, as was the Egyptian parties and the press a large role in stirring public opinionagainst the Italian occupation of Ethiopia.